In Situ Constructed P–N Junction on Cu2O Nanocubes through Reticular Chemistry for Simultaneously Boosting CO2 Reduction Depth and Ameliorating Photocorrosion. Issue 1 (23rd September 2021) - Wei, Zhihe; Mu, Qiaoqiao; Li, Xian; Yuan, Xuzhou; Su, Yanhui; Deng, Zhao; Peng, Yang; Shen, Mingrong
Abstract : Photocatalytic CO2 conversion into value‐added chemicals is the one‐stone–two‐birds approach to help meet the carbon neutral goal of near future, and lies on the development of competent photocatalysts that efficiently generate and separate the electron‐hole pairs. Herein, through reticular chemistry a p–n heterojunction is constructed on Cu2 O nanocubes by in situ transforming the surface to metal–porphyrin coordination polymer. The resulted Cu2 O@Cu‐TCPP core–shell heterostructure, when used for catalyzing CO2 reduction, exhibits not only improved activity, but also enhanced reduction depth. This boosted reducing power is attributed to the improved charge separation efficiency and thus populated charge carriers, as a result of the built‐in electron field of the p–n heterojunction. In addition, the Cu‐TCPP coating serves as a protecting sheath to mitigate the self‐corrosion of Cu2 O. Consequently, this study opens a new avenue of photocatalyst design and fabrication for simultaneously promoting multielectron products and ameliorating photocorrosion issues. Abstract : p‐Cu2 O/n‐Cu‐TCPP core–shell structure is constructed through in situ surface conversion. The heterostructure exhibits improved CH4 yield in photocatalytic CO2 reduction, and the boosted reducing power is attributed to the built‐in electric field of p–n junction.